Latina a řečtina v slovní zásobě, gramatice a terminologii slovanských jazyků - Žaža, Stanislav (Masarykova univerzita, 2010)
The book describes the results of influence of the ancient languages - Latin and Greek - upon the vocabulary, terminology, morphology, and syntax of various Slavonic languages.